A new strategy for total auricular reconstruction using prelamination of an extended retroauricular flap with tissue expansion. Issue 6 (June 2016) - Li, Chuan; Jiang, Haiyue; Huang, Chenyu; Chen, Jingning; Wu, Rongwei; Bi, Ye; Yang, Meirong; Zhang, Ye; Pan, Bo
Summary: Background and aim: To accomplish total ear reconstruction with aesthetic appearance is a great challenge for plastic surgeons worldwide due to insufficient skin coverage. A retroauricular fascial flap and skin graft technique are commonly used, but the results obtained are not satisfactory due to color mismatch, severe edema, and donor-site morbidity. Here, we describe a novel strategy for total ear reconstruction, utilizing an extended retroauricular flap prelaminated with tissue expansion to obtain enough skin for ear reconstruction. Methods: About 2 months before ear reconstruction, a kidney-shaped tissue expander was inserted at the mastoid region subcutaneously. The retroauricular skin became enlarged and thinner in 2 months after expansion. Next, the expander was removed and the retroauricular flap was extended by dissecting the surrounding scalp subcutaneously. By mobilizing the scalp-extended retroauricular flap, we could encapsulate the entire framework with thin and non-hair-bearing skin. Results: From August 2014 to September 2015, 36 microtia patients had undergone ear reconstruction using the novel strategy. Satisfactory aesthetics along with fine structure, symmetry, and maintenance of the auriculocephalic angle was achieved in all patients. Conclusions: Using our novel strategy, we can obtain satisfactory aesthetic outcomes by fully mobilizing the expanded skin without additional morbidities of the donor sites. Patients are satisfied with the vivid ear contour and lack of groin scar.